The Effect of Sense of Place Towards Social Capital on Millennials in A Semi-Urban City (A Case Study in Padang, West Sumatera - Indonesia) - Hafrizal Okta Ade Putra; Werry Darta Taifur; Donard Games; Hefrizal Handra (Ilomata International Journal of Social Science, 2023)
The millennials, as other generations, has their own characteristics that can be seen from their traits, habits, lifestyle, and nature which due to those attributes can lead to different expectations from others. This research aims to understand and analyse the effect of sense of place towards social capital on millenials in a semi-urban city. The population of this study is the Millennial generation in Padang aged 19 to 38 years with a total population of 425,053 people. The number of samples was determined using the formulation proposed by Slovin (1960), namely 400 respondents from various backgrounds, ages, education, domicile, profession, and income were involved. Based on the result of hypothesis testing, it was found that sense of place has a positive and significant influence towards social capital. This research is expected to carry a positive contribution to the dynamics, issues, and problems of millennials related to sense of place and social capital, especially in a semi-urban city in developing countries.